New indications for exenatide therapy of type 2 diabetes mellitus - Olga Konstantinovna Vikulova; Marina Vladimirovna Shestakova (Сахарный диабет)
Obesity associated with the enhanced risk of cardiovascular disorders plays a key role in the evolvement and progression of type 2 diabetes mellitus(DM2). Incretin mimetics are the sole class of hypoglycemic agents that not only effectively correct hyperglycemia but also reduce body weight. Exenatide(Byetta) is the first drug of this class approved for the use as monotherapy. This paper presents a detailed review of the available data on thescope of exenatide effects and the results of its clinical studies that confirm high efficiency of Byetta used for both monotherapy and combined therapyof DM2.